STRATEGI PENGEMBANGAN AGRIBISNIS JAGUNG DI KECAMATAN AMPANA TETE KABUPATEN TOJO UNA-UNA - Musna Mohamad; Max Nur Alam; Rustam Abd Rauf (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
The research was conductedin Ampana Tete sub district of Tojo Una-Una regency. This research aimed to(1)determine the income of corn farming system,and (2) determine the development strategy for developing corn agribusiness in Ampana Tete sub district of Tojo Una-Una Regency. Samples were taken by a random sampling method. Fourty respondents were selected from farmer population of 357 people. The tools for data analysis were income, SWOT and QSPM analysis. The income of the farming system was found to be IDR 6,143,974/ha/planting season in average. SWOT analysis results indicated that the appropriate strategy in the development of agribusiness corn is a S-O strategy (Strength-Opportunities) supporting an aggressive strategy, with strategy formulation (1) increaseing production by using or adopting appropriate agricultural technologies, (2) increasing land potency and utilizing government support to increase production; and (3) creating partnership with the industry or government to obtain market and equipments needed. The QSPM analysis results suggested that the best strategy is that increasing production by using or adopting appropriate agricultural technologieswith a total value of attractiveness (TAS) of 5.850Keywords: Corn Agribusiness, development strategy, and income.